Determining the cost of genital warts: a study from Ireland. Issue 5 (12th November 2008) - Dee, A; Howell, F; O'Connor, C; Cremin, S; Hunter, K
Abstract : Objectives: To determine the average cost of a case of genital warts, for both males and females, with a view to informing the current debate as to which Human papillomavirus vaccine would have maximum cost-effectiveness in the Irish population. Methods: Contact time between patients and healthcare professionals was prospectively measured at five genitourinary medicine clinics in the south-west of Ireland, over a period of 3 weeks. By identifying all those with genital warts, it was possible to calculate the proportion of total time taken by patients with this condition, and from this to calculate a cost per incident case, by gender. Results: A total of 25.5% of attendances were for genital warts, and these patients used 26.2% of total clinic time (CI 25.4 to 27.0%). The average cost calculated for genital warts was €335 per incident case, and by gender €300 per male case and €366 per female case. Conclusions: There are considerable costs associated with the treatment of genital warts, with female cases representing a higher cost than males. By vaccinating with the quadrivalent HPV vaccine, there are significant savings to be made.